Arah Kebijakan One Map Policy dalam Percepatan Reforma Agraria: Upaya Penyelesaian Konflik Agraria - Aprillia Wahyuningsih (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The state's agenda in fulfilling the needs of its people is one of them by carrying out various developments by utilizing natural resources. This is done by utilizing existing land in the territory of Indonesia. However, the number of state institutions in the implementation of development often results in conflicts. One of the causes of the conflict is overlapping land tenure by the community, government and private sector. Thus, in order to prevent and resolve agrarian conflicts, it is necessary to harmonize land use maps that are integrated on one map. This study intends to provide an introduction to the discussion regarding the importance of one map policy in accelerating agrarian reform as an effort to resolve agrarian conflicts. The research method used in this research is normative research and uses statutory and conceptual approaches. The results of this study show the following: One Map Policy is a government policy that can support the agrarian reform program and resolve overlapping land conflicts which are carried out with the aim of achieving legal certainty and protection as well as justice and prosperity for all Indonesian people.